2012
DOI: 10.1039/c2cp24135h
|View full text |Cite
|
Sign up to set email alerts
|

Surface-enhanced Raman scattering of 4,4′-dimercaptoazobenzene trapped in Au nanogaps

Abstract: The surface-enhanced Raman scattering (SERS) of 4,4'-dimercaptoazobenzene (4,4'-DMAB), an alpha, omega-dithiol possessing also an azo moiety, has seen a surge of interest recently, since 4,4'-DMAB might be able to form from 4-aminobenzenethiol (4-ABT) via a surface-induced photoreaction. An understanding of the intrinsic SERS characteristics of 4,4'-DMAB is thus very important to evaluate the possibility of such a photoreaction. We found in this work that 4,4'-DMAB should adsorb on a flame-annealed Au substrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
51
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(59 citation statements)
references
References 40 publications
7
51
1
Order By: Relevance
“…Previous studies found that the SERS spectrum of PATP could change under effects of pH of solution and power of excitation . In this work, we re‐investigated the effects of solution pH value and excitation powe on the SERS spectra PATP and DMAB.…”
Section: Introductioncontrasting
confidence: 59%
See 3 more Smart Citations
“…Previous studies found that the SERS spectrum of PATP could change under effects of pH of solution and power of excitation . In this work, we re‐investigated the effects of solution pH value and excitation powe on the SERS spectra PATP and DMAB.…”
Section: Introductioncontrasting
confidence: 59%
“…However, the opposite results were gotten in previous literatures, i.e. the b 2 mode bands of PATP SERS spectra vary drastically with the measurement conditions …”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…As shown in Fig. 2 a and b, conversion of 4ATP into DMAB can be clearly distinguished from the new Raman bands that appear at 1140 cm −1 due to β (CH), and 1390 and 1432 cm −1 due to ν (N = N)18. The reaction will be terminated at a point when no obvious intensity changes of the DMAB Raman bands are observed.…”
Section: Resultsmentioning
confidence: 86%